2-[(4-Chlorophenyl)sulfanyl]-2-methoxy-1-phenylethan-1-one: crystal structure and Hirshfeld surface analysis - Caracelli, Ignez; Zukerman-Schpector, Julio; Traesel, Henrique J.; Olivato, Paulo R.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2018)
The title compound, C15H13ClO2S, comprises (4-chlorophenyl)sulfanyl, benzaldehyde and methoxy residues linked at a chiral methine-C atom (the crystal is racemic). A twist in the methine-C—C(carbonyl) bond [O—C—C—O torsion angle = 19.3 (7)⁰] leads to a dihedral angle of 22.2 (5)⁰ between the benzaldehyde and methine+methoxy residues. The chlorobenzene ring is folded to lie over the O atoms, with the dihedral angle between the benzene rings being 42.9 (2)⁰. In the crystal, the carbonyl-O atom accepts two C—H...O interactions with methyl- and methine-C—H atoms being the donors. The result is an helical supramolecular chain aligned along the c axis; chains pack with no directional interactions between them. An analysis of the Hirshfeld surface points to the important contributions of weak H...H and C...C contacts to the molecular packing.